(untitled) (Вестник Пермского университета. Серия «Химия», 2019)
The reactions of 3-aroyl-1H-pyrrolo[2,1-c][1,4]benzoxazine-1,2,4-triones with a number of Gewald thiophenes were studied. It was established that as a result of these reactions, substituted (Z)-ethyl 2(2,4-dioxo-3-(2-oxo-2H-benzo[b][1,4]oxazin-3(4H)-ylidene)-4-arylbutanamido)thiophene-3-carboxylates